2007
DOI: 10.1182/blood-2007-05-087403
|View full text |Cite
|
Sign up to set email alerts
|

CCR1/CCL5 (RANTES) receptor-ligand interactions modulate allogeneic T-cell responses and graft-versus-host disease following stem-cell transplantation

Abstract: Acute graft-versus-host disease (GVHD) and leukemic relapse are serious complications of allogeneic stem-cell transplantation (SCT). Recruitment of activated T cells to host target tissues or sites of leukemic infiltration (graft-versusleukemia [GVL]) is likely mediated by chemokine receptor-ligand interactions.We examined the contribution of donor cell CCR1 expression to the development of GVHD and GVL using a well-established murine SCT model (B6 3 B6D2F1) and CCR1-deficient mice (CCR1 ؊/؊ ). Allo-SCT with C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
70
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 72 publications
(74 citation statements)
references
References 68 publications
(102 reference statements)
2
70
2
Order By: Relevance
“…11,[25][26][27]50,68 As suggested by Wysocki et al, 32 cellular sources of chemokines may differ between specific target organs. Our results showing peak CCL3 expression in the gut and tongue early after allo-BMT, followed by a continuous decline, strengthen the concept that increased CCL3 production in these organs derives from host cells, 50 whereas in contrast, the observed increase in CCL3 expression in the liver and lung over the first 3 Figure 7 Chemokine expression is increased both on mRNA and on protein levels in aGVHD target organs after allogeneic BMT.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…11,[25][26][27]50,68 As suggested by Wysocki et al, 32 cellular sources of chemokines may differ between specific target organs. Our results showing peak CCL3 expression in the gut and tongue early after allo-BMT, followed by a continuous decline, strengthen the concept that increased CCL3 production in these organs derives from host cells, 50 whereas in contrast, the observed increase in CCL3 expression in the liver and lung over the first 3 Figure 7 Chemokine expression is increased both on mRNA and on protein levels in aGVHD target organs after allogeneic BMT.…”
Section: Discussionmentioning
confidence: 96%
“…Increased expression of a number of chemokines and chemokine receptors in GVHD target organs has been described earlier, [18][19][20][21] and previous studies have further shown that targeting one specific chemokine or chemokine receptor can result in the reduction of aGVHDrelated injury to various target organs. 11,[22][23][24][25][26][27][28][29][30][31][32] Interestingly, tropism and efficacy of such a strategy differed depending on the chemokine and/or the chemokine receptor involved, 33 suggesting that the enhanced expression of chemokines after allo-BMT may differ between organs with respect to quality, quantity and kinetics.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Such chemotactic effects have been shown to be relevant for leukemia control. 45,46 Of note, some of these soluble factors are typically produced by antigen-specific CD8 þ T-cells during viral infections and are associated with anti-viral processes. Indeed, a causative role for infections with herpes viruses has already been postulated in the pathogenesis of LGL expansions.…”
Section: Discussionmentioning
confidence: 99%
“…5). Interestingly, both cytokines have previously been shown to be critically involved in allograft rejection, GVHD, and autoimmunity (67)(68)(69)(70)(71)(72)(73)(74).…”
Section: Discussionmentioning
confidence: 99%